Financial Performance and Valuation Analysis of Diversification Company in Indonesia Case Study: PT. Harum Energy Tbk (HRUM) - Danyaa Allya Salsabilla; Raden Aswin Rahadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The planned termination of coal-fired power plants (PLTU) and the ongoing energy transition are set to significantly reshape Indonesia's energy sector. This shift is expected to lead to a marked decrease in coal demand. In response to these changes, several coal companies in Indonesia are diversifying their operations into green energy enterprises. The Indonesian government has introduced various incentive packages designed to promote the construction of nickel smelters and processing facilities. PT Harum Energy, a company that focused on coal but has significantly expanded its operations by acquiring nickel mines and smelters. Despite the promising prospects of nickel, HRUM faced a dramatic 99% decline this year. Apart from that, HRUM's share price has exhibited considerable volatility since the diversification began. The objective of this study is analyze financial performance during diversification and evaluate the intrinsic value of HRUM to give recommendation to the investors in making decisions in the current market. The methods utilized are secondary data by looking at historical data for the last 5 years through the 2019-2023. The author applies the DCF-FCFF method to determine the intrinsic value, which is calculated at IDR 570. With the current market price of IDR 1,130, the stock is perceived to be overvalued as its market price exceeds its intrinsic value. Further analysis is also carried out using relative valuation, which the P/E ratio, P/B ratio, and EV/EBITDA ratio is overvalued compared to the industry average. Therefore, the author does not recommend prospective investors to buy shares at this time.